2021
DOI: 10.3390/nu13082839
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Bacteria Composition of Healthy Men with the Same Nutritional Profile Undergoing 10-Week Aerobic Exercise Training: A Randomized Controlled Trial

Abstract: Nutrient consumption and body mass index (BMI) are closely related to the gut microbiota, and exercise effects on gut bacteria composition may be related to those variables. Thus, we aimed to investigate the effect of 10-week moderate aerobic exercise on the cardiorespiratory fitness and gut bacteria composition of non-obese men with the same nutritional profile. Twenty-four previously sedentary men (age 25.18 [SD 4.66] years, BMI 24.5 [SD 3.72] kg/m2) were randomly assigned into Control (CG; n = 12) or Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 62 publications
0
48
0
Order By: Relevance
“…29 The genus Bifidobacterium, main member of the family Bifidobacteriaceae, has been associated to improved sport performance and lower plasma levels of parameters associated to fatigue, such as lactate, ammonia, creatine kinase, and inflammatory biomarkers, like pro-inflammatory cytokines, without changes in SCFA production. 30 31 In addition, Erysipelotrichaceae was found to be associated with VO 2 peak, due to its ability to increase butyrate production, 32 while Sutterella, the main genus belonging to the family Sutterellaceae, has been positively associated with this parameter through its effect on antioxidant defences 33 . Therefore, despite being well known SCFA producers, the mechanism by which these families are related to performance improvements is not only mediated by their ability to produce SCFAs, but also other metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…29 The genus Bifidobacterium, main member of the family Bifidobacteriaceae, has been associated to improved sport performance and lower plasma levels of parameters associated to fatigue, such as lactate, ammonia, creatine kinase, and inflammatory biomarkers, like pro-inflammatory cytokines, without changes in SCFA production. 30 31 In addition, Erysipelotrichaceae was found to be associated with VO 2 peak, due to its ability to increase butyrate production, 32 while Sutterella, the main genus belonging to the family Sutterellaceae, has been positively associated with this parameter through its effect on antioxidant defences 33 . Therefore, despite being well known SCFA producers, the mechanism by which these families are related to performance improvements is not only mediated by their ability to produce SCFAs, but also other metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Allen et al [ 33 ] did not observe statistical differences between the α-diversity of lean and of obese participants at baseline or after 6 weeks of endurance-based exercise training [ 33 ]. Moreover, Resende et al [ 34 ] reported no differences in α-diversity in 24 previously sedentary men after 10 weeks of aerobic exercise training. Therefore, our observation of an increasing α-diversity after the training program implemented for 7 weeks prior to the season’s best performances is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, three studies compared data to an apparently healthy population [ 33 , 34 , 36 ], with the rest comparing exercise groups [ 35 , 40 , 41 ], waitlist or crossover [ 37 , 38 , 39 , 42 ], control groups [ 43 , 44 , 45 ] or did not include a comparison [ 30 , 31 , 32 ]. Of the remaining 12 ‘healthy population’ studies, four included apparently healthy sedentary and recreationally active participants [ 20 , 27 , 28 , 29 ]; one study was in a military setting [ 21 ], and seven studies assessed athletes only [ 18 , 19 , 22 , 23 , 24 , 25 , 26 ]. The mean age was 35.4 ± 13.1 years, and the mean BMI was 26.0 ± 3.8 kg/m 2 (41.3 ± 12.7 years and 27.8 ± 3.38 kg/m 2 for the clinical population studies, respectively; the mean age and BMI for the apparently healthy populations were 28.9 ± 10.6 years and 23.8 ± 2.7 kg/m 2 , respectively).…”
Section: Participant Characteristicsmentioning
confidence: 99%